2020
DOI: 10.1097/iae.0000000000002385
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Gene Expression Profile Status and American Joint Commission on Cancer Stage in Uveal Melanoma

Abstract: Purpose: To study the relationship between gene expression profile (GEP) sub-class and AJCC stage in uveal melanoma (UM) patients. Methods: A retrospective, multi-center study was undertaken with patients entered from 9 major ocular oncology centers from across the United States. 360 eligible patients had UM and underwent I-1 2 5 plaque brachytherapy with concurrent tumor biopsy with GEP testing between January 1, 2010 and October 28, 2014. Patient demographics and UM features were analyzed by both GEP and AJC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…There is a documented discordance between clinical cancer staging and molecular prognostic results [8]. We observed that 80% of AJCC stage III melanomas were GEP class 2 and half of AJCC stage I and II melanomas were GEP class 1A.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…There is a documented discordance between clinical cancer staging and molecular prognostic results [8]. We observed that 80% of AJCC stage III melanomas were GEP class 2 and half of AJCC stage I and II melanomas were GEP class 1A.…”
Section: Discussionmentioning
confidence: 77%
“…Prognostic information such as the GEP has been shown to alter the surveillance strategies and referral patterns of physicians caring for patients with UM [7]. While it has been shown that higher risk GEP class and higher risk AJCC cancer stage are often correlated at presentation [8], the prognostic outcomes of the 2 entities are not always in agreement. When discordant, it becomes challenging to determine an appropriate surveillance strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Berry et al . stratified 360 melanoma patients into AJCC stages 1, 2, and 3 as well as GEP class and discovered that there was a significant correlation between larger tumor dimensions (both LBD and thickness) and class 2 status ( P <0.05) 144 . Moreover, larger AJCC tumor groups had a significantly higher odds ratio of having a worse prognosis based on the corresponding GEP class.…”
Section: Uveal Melanomamentioning
confidence: 99%
“…GEP allows for the classification of primary uveal melanomas into Class 1A (low metastatic risk), Class 1B (intermediate risk) and Class 2 (high risk) [19,20]. We have previously demonstrated that Class 1 tumors respond faster to radiation therapy as seen by a decrease in tumor height, described practice patterns with regard to tumor biopsy technique, and correlated GEP with American Joint Commission on Cancer Staging [21,22]. Here we report practice patterns for patients treated for uveal melanoma with I-125 plaque brachytherapy who concurrently underwent fine-needle aspirate biopsy for GEP testing of the melanoma, as well as current practice patterns at OOSC institutions as determined by a 2018 survey.…”
Section: Introductionmentioning
confidence: 99%